Podiatric assessment in children and adults with epidermolysis bullosa: are foot and ankle patient-reported outcome measures (PROMs) able to measure the severity of podiatric involvement among EB patients? - Joy Lynn Wong; Mohammed Tariq Khan, PhD, BSc (Hons), BSc (PodMed), CSci, MRCPod, FRCPodM, FFPM RCPS (Glasgow), FLS; Timothy L. Cowan, BSc, MBBS (Hons); Dedée F. Murrell, MA, BMBCh, FAAD, MD, FACD, FRCP(Edin) (International Journal of Women's Dermatology, 2023)
Epidermolysis bullosa (EB) represents a group of rare genetic skin fragility disorders characterized by (muco) cutaneous blistering upon minimal mechanical trauma. Ninety percent of EB patients experience podiatric symptoms which may affect physical functioning and emotional well-being. To date, an EB-specific podiatric assessment has not been outlined to guide clinicians in the assessment of EB podiatric involvement. This review describes the podiatric involvement of patients with EB and assesses the relevance of validated foot and ankle patient-reported outcome measures (PROMs) in measuring podiatric severity among EB patients. A literature review was conducted to identify systematic reviews and clinical studies investigating foot health and podiatric manifestations using validated foot health PROMs across foot and ankle conditions. Limited studies have documented the significance of podiatric involvement among EB patients. Existing EB-specific PROMs are not region-specific for assessing podiatric involvement. Among the foot and ankle PROMs, the Foot Health Status Questionnaire, Foot Function Index, and Manchester Oxford Foot Questionnaire were identified as potentially appropriate for assessing podiatric severity among EB patients, each with its strengths and limitations in assessment. However, they have not been widely validated for assessing dermatology-related diseases. An evaluation of the relevance of each identified PROM to EB podiatric assessment would enable future development of an appropriate EB-specific podiatric assessment tool that would guide management.